2006
DOI: 10.1074/jbc.m603487200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Caspase-9 Provides Genetic Evidence for the Type I/II Concept of CD95-mediated Apoptosis

Abstract: The death receptor CD95 triggers apoptosis upon formation of a death-inducing signaling complex and the activation of caspase-8. Two types of CD95-mediated apoptosis have been distinguished that differ in their efficiency of death-inducing signaling complex formation and the requirement of mitochondria for caspase activation. The validity of the type I/II model, however, has been challenged, as Bcl-2 expression or the use of various CD95 agonists resulted in different apoptosis effects. By identifying a caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 35 publications
5
57
1
1
Order By: Relevance
“…12 --14 Originally described for CD95, different cell types respond to death ligands as either; type I cells, which rapidly form large amounts of DISC and activate caspase-8 and -3 directly or type II cells, where comparatively small amounts of DISC are formed and the intrinsic pathway is activated by cleaved Bid. 15 Type I and II responses have also been described for TRAIL where blockade of the mitochondrial amplification arm by either over-expression of anti-apoptotic Bcl-2/Bcl-X L , 16 or knockout of caspase-9 17 or Bax 18 attenuates TRAIL-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…12 --14 Originally described for CD95, different cell types respond to death ligands as either; type I cells, which rapidly form large amounts of DISC and activate caspase-8 and -3 directly or type II cells, where comparatively small amounts of DISC are formed and the intrinsic pathway is activated by cleaved Bid. 15 Type I and II responses have also been described for TRAIL where blockade of the mitochondrial amplification arm by either over-expression of anti-apoptotic Bcl-2/Bcl-X L , 16 or knockout of caspase-9 17 or Bax 18 attenuates TRAIL-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…To extend our studies from a nonmalignant murine cell line to human leukemic cells, we used Jurkat T-cells deficient in caspase-9 and the same cells reconstituted with caspase-9, as a control. 26,27 Caspase-9 is the initiator caspase in the intrinsic pathway and if apoptosis occurs through this pathway, it cannot proceed in the absence of caspase-9. Cell death was assessed by PS externalization for all the compounds except obatoclax.…”
Section: Cell Death Induction In Mefs Deficient In Bax Andmentioning
confidence: 99%
“…The role of caspase-9 in Fas-mediated cell death of Jurkat cells upon stimulation with cross-linked FasL has been controversial. Previous studies suggested a partial or dispensable role of caspase-9 in this process (44)(45)(46). We found distinct requirements for FADD, caspase-8, and caspase-9 in CSup-triggered cell death associated with Fas-dependent apoptosis.…”
Section: Enzymatic and Molecular Characterization Of Csup-induced Celmentioning
confidence: 51%